Injuries in Korean elite taekwondo athletes: A prospective study - Son, B.; Cho, Y. J.; Jeong, H. S.; Lee, S. Y. (International Journal of Environmental Research and Public Health, 2020)
This prospective cohort study aimed to identify the incidence and characteristics of Taekwondo-related injuries according to age, sex, and event type (i.e., practice or competition) based on a web-based injury surveillance system (ISS) with a follow-up period of 12 months. A total of 285 members of the Korea Taekwondo Association who competed in the 2016 season participated. Injury incidence rates (IRs) were calculated per 1000 athlete-exposures (AEs). Injury rate ratios (RRs) with 95% confidence intervals were calculated and compared regarding age, sex, and event type. During the season, 336 injuries were reported, resulting in a rate of 6.31/1000 AEs. The most common location, type, and mechanism of injury in Taekwondo athletes were the foot/ankle, ligament sprain, and contact with another player, respectively. The overall injury IRs associated with Taekwondo practicing and competition were 4.79/1000 AEs and 24.86/1000 AEs, respectively. The overall injury RR related to both practice and competition was higher in youth athletes than in adult athletes. However, adult athletes were more likely to sustain more severe injuries. Korean elite Taekwondo athletes were commonly exposed to injury, especially youth and female athletes. Therefore, continuation of the ISS suggests the development of interventions for preventing injuries sustained by Taekwondo athletes